2014
DOI: 10.1007/s00300-014-1537-3
|View full text |Cite
|
Sign up to set email alerts
|

The cosmopolitan moss Bryum argenteum in Antarctica: recent colonisation or in situ survival?

Abstract: Since the onset of glaciation following the Oligocene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 57 publications
2
71
2
Order By: Relevance
“…In a review of European Holocene bryophyte history, Kyrkjeeide et al (2014) found no cases of unambiguous evidence for in situ survival within the area of the Scandinavian ice sheet. This is in contrast to evidence of in situ survival of Antarctic populations of the moss Bryum argenteum (Pisa et al 2014) as well as an increasingly wide range of Antarctic microorganisms and invertebrates (Convey et al 2008(Convey et al , 2009Pointing et al 2015).…”
Section: Could Bryophytes Have Persisted In Situ?contrasting
confidence: 87%
“…In a review of European Holocene bryophyte history, Kyrkjeeide et al (2014) found no cases of unambiguous evidence for in situ survival within the area of the Scandinavian ice sheet. This is in contrast to evidence of in situ survival of Antarctic populations of the moss Bryum argenteum (Pisa et al 2014) as well as an increasingly wide range of Antarctic microorganisms and invertebrates (Convey et al 2008(Convey et al , 2009Pointing et al 2015).…”
Section: Could Bryophytes Have Persisted In Situ?contrasting
confidence: 87%
“…As with marine groups, substantial cryptic diversity has been unveiled in the terrestrial metazoan biota 42,45 and its diversity is likely much higher than is currently 7 appreciated. Moreover, for most groups, including those that are considered well known, the full extent and structure of the continent's diversity remains partially understood because much of it has not been thoroughly surveyed 46 .…”
Section: Diversity In the Terrestrial Biotamentioning
confidence: 99%
“…With the onset of the ACC came circumpolar thermal fronts such as the Subtropical Front (STF) and Antarctic Polar Front (APF) (Fig. 1) 45,46 .…”
Section: Diminishing Isolation 12mentioning
confidence: 99%
“…Fraser et al (2014) suggest that the present biodiversity is linked to the presence of geothermal areas offering refugia through past more extensive glaciation periods. In contrast, Pisa et al (2014) suggest that several colonisation events have occurred for the cosmopolitan moss Bryum argenteum, and Hills et al (2010) suggest Pleistocene survival for the same species. Green et al (2011a) also suggest relict occurrence of several species in the Beardmore Glacier area, 83°S.…”
Section: Introductionmentioning
confidence: 83%
“…Torricelli et al (2010) suggest that their results confirm the likelihood of a pre-Pleistocene origin for Antarctic springtails, which must have survived the glacial periods in multiple refugia in each of the major regions where they are currently found. Mosses are suggested to have recolonised the Ross Sea region at around 3.5 Ma (Pisa et al 2014), and this follows the major glaciations of the Miocene and also the volcanic activity and formation of the region around Cape Hallett dated at 5.49 ± 0.12 and 6.6 ± 0.4 Ma (McIntosh and Kyle 1990).…”
Section: Discussionmentioning
confidence: 98%